Pharmacological Activities of Olea europaea Leaves. Issue 6 (22nd September 2014) - Ben Salem, Maryem; Affes, Hanen; Ksouda, Kamilia; Sahnoun, Zouheir; Zeghal, Khaled Mounir; Hammami, Serria
Abstract: Olive tree leaves ( O lea europaea  L.) have been widely used in traditional remedies as extracts, herbal teas and powder in European and Mediterranean countries. Bioactivities of olive tree were obtained by product extracts. They were attributing to antioxidant and phenolic components such as oleuropein, hydroxytyrosol, tyrosol and ligstroside. Studies were indicating that biologically active compounds in olive leaves products were effective in treating different disorders. Several studies have been showing that oleuropein (up to 6–9% of dry matter in the leaves) possesses a wide range of pharmacological and health‐promoting properties including antiarrhythmic, spasmolytic, immune stimulant, cardioprotective, hypotensive, antioxidant and anti‐inflammatory effects. Practical Applications: O lea europaea preparations have been widely used in folk medicine in different countries. The medicinal parts of the olive tree were the leaf extracts. Many researchers have been searching for olive leaves subproducts that could have beneficial effects on human health. In the present review, compounds obtained from olive leaf extracts had been subject to numerous investigations of their therapeutic properties.